Revision of the spider genus Stygopholcus (Araneae, Pholcidae), endemic to the Balkan Peninsula - Huber, Bernhard A.; Pavlek, Martina; Komnenov, Marjan (European Journal of Taxonomy, 2021)
The genus Stygopholcus Kratochvíl, 1932 is endemic to the Balkan Peninsula and includes only four nominal species: the epigean S. photophilus Senglet, 1971 in the south (Greece to Albania) and the ‘northern clade’ consisting of three troglophile species ranging from Croatia to Albania: S. absoloni (Kulczyński, 1914); S. skotophilus Kratochvíl, 1940; and S. montenegrinus Kratochvíl, 1940 (original rank re-established). We present redescriptions of all species, including extensive data on ultrastructure, linear morphometrics of large samples, and numerous new localities. We georeference previously published localities as far as possible, correct several published misidentifications, and clarify nomenclatorial problems regarding the authority of Stygopholcus and the identity of the type species S. absoloni. We suggest that the ‘northern clade’ has a relict distribution, resulting from past and present geologic and climatic factors. Future work on Stygopholcus should focus on the southern Dinarides, combining dense sampling with massive use of molecular data.